2016
DOI: 10.1159/000446219
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus in Europe and Safety of Blood Transfusion

Abstract: West Nile virus (WNV) has become an increasing issue in the transfusion setting since 2002, when it was firstly shown in the USA that it can be transmitted through blood transfusion. Since then, several precautionary measures have been introduced in Europe in order to reduce the possible risk of transmission via transfusion/solid organ transplantation. In addition, the epidemiological surveillance has been tightened and the network for communication of human WNV cases strengthened. This review will focus on WN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 52 publications
(47 reference statements)
0
54
0
7
Order By: Relevance
“…This also fits with the lack of cases in donors; no donation has been confirmed to be WNV‐positive. Germany, another non‐affected area, also experienced zero confirmed WNV positives in their first season of testing, with 0·9% of blood donations tested where donors had mainly travelled to Italy, Croatia, Greece and the United States (Dreier et al, ), whereas Italy, with affected areas, identified 57 of 1144675 donations as positive (0·005%, range 0·00–0·01%) between 2011 and 2015 (Pisani et al, ). NHSBT, which tests donations for WNV in a non‐affected country, have considered that testing in pools of six continues to ensure that the required level of sensitivity is maintained in a cost‐effective way rather than move to singleton testing.…”
Section: Discussionmentioning
confidence: 99%
“…This also fits with the lack of cases in donors; no donation has been confirmed to be WNV‐positive. Germany, another non‐affected area, also experienced zero confirmed WNV positives in their first season of testing, with 0·9% of blood donations tested where donors had mainly travelled to Italy, Croatia, Greece and the United States (Dreier et al, ), whereas Italy, with affected areas, identified 57 of 1144675 donations as positive (0·005%, range 0·00–0·01%) between 2011 and 2015 (Pisani et al, ). NHSBT, which tests donations for WNV in a non‐affected country, have considered that testing in pools of six continues to ensure that the required level of sensitivity is maintained in a cost‐effective way rather than move to singleton testing.…”
Section: Discussionmentioning
confidence: 99%
“…This may also apply for countries endemic for ZIKV. After the WNV outbreak, some European countries have introduced a selectively WNV NAT based on travel history . The risk of a ZIKV outbreak in Europe is feasible since one of its vectors, Ae.…”
Section: Discussionmentioning
confidence: 99%
“…After the WNV outbreak, some European countries have introduced a selectively WNV NAT based on travel history. 31 The risk of a ZIKV outbreak in Europe is feasible since one of its vectors, Ae. albopictus, is present in South Europe and ZIKV imported cases into Europe have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Screening for WNV by nucleic acid test was implemented in the United States in 2003. Since 2004, blood centres in the EU have been obliged to either defer donors for 28 days after travelling to or living in endemic areas or implement blood screening procedures .…”
Section: Some Current Eids Relevant For Blood Safetymentioning
confidence: 99%